KKN KBM Berbasis Masjid Sebagai Model Trauma Healing Berkelanjutan Pasca Gempa di Lombok Utara - Mujiburrahman Mujiburrahman; Masjudin Masjudin; Dedi Irawan; M. Zaenudin; Waini Septiana; Suhaini Suhaini; Irwansyah Irwansyah (Sasambo: Jurnal Abdimas (Journal of Community Service), 2019)
The earthquake that shook the Lombok Island in 2018 caused an impact of physical and psychological damage to the community. Especially in the village of Persiapan Menggala, many children experience fear, anxiety, sadness, and even prolonged trauma. Therefore, the community of Persiapan Menggala Village, especially children, is in dire need of a psychological rehabilitation process. One effort that can be done in helping to reduce community trauma is to do trauma healing. Trauma healing is very important especially for children affected by disasters. Therefore, the purpose of this community service activity is to carry out trauma healing that is ongoing for the children of the village of Persiapan Menggala, Pemenang sub-district, North Lombok Regency. The trauma healing service was carried out by holding a Mosque-based Teaching and Learning Activity (KBM). This activity is carried out by involving students doing a Real Work Lecture (KKN) of the village of Persiapan Menggala for 30 days. Activities undertaken include (1) Study Dex (2) compiling mosque-based curriculum for teaching and learning; (3) carrying out debriefing to students; (4) implementing mosque-based KBM; (5) holding competition activities; (6) opinion polls on community responses to mosque-based teaching and learning activities. The impact of this activity was very positive for the children of the Persiapan Menggala village, namely the reduction of fear, anxiety, sadness, and even trauma experienced and the increase in the noble character and knowledge of religion, mathematics, and science of the children of the Persiapan Menggala village.